Examen especial a los ingresos y gastos corrientes del Gobierno Autónomo Descentralizado Municipal del cantón Ventanas, período 2022 - Angulo Vásconez, Darwin Javier (2025)
Managing current revenues and expenditures in Decentralized Autonomous Governments (GAD) is essential for financial sustainability and the effective execution of public projects. This study focuses on the "Special review of current revenues and expenditures of the Municipal Decentralized Autonomous Government of Ventanas Canton, 2022". Its objective is to evaluate the efficiency and effectiveness of managing municipal resources. A qualitative methodology was applied, using both documentary and field research. Key findings revealed several deficiencies: irregular cash flow monitoring, inconsistent application of Governmental Accounting Standards, and the absence of surprise cash counts. These issues negatively impact financial planning, accounting accuracy, and transparency. As a result, the study recommends establishing clear procedures for cash flow usage, ensuring proper application of accounting norms, and implementing regular surprise audits to enhance accountability in public administration